EMOTIONAL INTELLIGENCE AND SELF-EFFICACY IN PERSONAL SELECTION CONTEXTS - García Izquierdo, Antonio León; García Izquierdo, Mariano; Ramos Villagrasa, Pedro José (Anales de Psicología / Annals of Psychology, 2007)
The aim of this paper is finding the added criterion referenced validity of emotional intelligence and self-efficacy as predictor variables of performance in a personnel selection simulation context over the big-five model of personality, aptitudes and biodata. We applied hierarchical and multiple regression models. Results obtained point that such variables present a significant association with criteria and predictive accuracy. However, the appropriate use of that variables depend on the particular criteria both professional and scientific, because the amount of gain is not high.